A flexible microassembly system based on hybrid manipulation scheme for manufacturing photonics components - Kim, B; Kang, HJ; Kim, DH; Park, JO (SPRINGER LONDON LTD, 2006)
In this paper, a flexible microassembly system based on hybrid manipulation scheme is proposed to apply to the assembly of photonics components such as lensed optical fiber ferrules and laser diode (LD) pumps. In order to achieve both high precision and dexterity in microassembly, we propose a hybrid microassembly system with sensory feedbacks of vision and force. This system consists of the distributed six degrees of freedom (DOF) micromanipulation units, the stereomicroscope, and haptic interface for the force feedback-based microassembly. A hybrid assembly method, which combines the vision-based microassembly and the scaled teleoperated microassembly with force feedback, is proposed. The feasibility of the proposed method is investigated via experimental studies for assembling micro-optoelectrical components. Experimental results show that the hybrid microassembly system is feasible for applications to the assembly of photonic components in the commercial market with better flexibility and efficiency.